THE EFFECT OF MODERNIZATION OF TAX ADMINISTRATION ON THE COMPLIANCE OF MOTOR VEHICLE TAXPAYERS (CASE STUDY OF SAMSAT GORONTALO CITY) - Esmelanda Diens; Hartati Tuli; Muliyani Mahmud (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to determine the influence of administrative modernization in taxation on the compliance of vehicle taxpayers at the SAMSAT Office in the Gorontalo City area. The modernization of tax administration is expected to increase service efficiency and convenience for taxpayers which can encourage increased compliance in fulfilling tax obligations. This study uses a quantitative method. Population in this study are all registered motor vehicle taxpayers as many as 144,490 taxpayers, with a sample of 100 respondents consisting of 83 two-wheeled vehicle taxpayers and 17 four-wheeled motor vehicle taxpayers. The sampling technique uses proportional random sampling. Data were collected through the distribution of questionnaires to taxpayers and analyzed using simple linear regression analysis and IBM SPSS 25. The results of the study show that the modernization of tax administration has a positive and significant effect on the compliance of motor vehicle taxpayers. This is evidenced by a t-calculated value of 2.514 > t-table of 1.98472 and a significance value of 0.014 < 0.05. The value of the regression coefficient of 0.129 indicates that every 1% increase in tax administration modernization will increase taxpayer compliance by 12.9%. In addition, a determination coefficient value (R2) of 0.061 indicates that 6.1% of the variation in taxpayer compliance can be explained by modernization of tax administration, while the remaining 93.9% is influenced by other factors outside of this study.